Sustainable corporate governance mediates between firm performance and corporate social responsibility using structural equation modelling - Imran, Muhammad; Liu, Xiangyang; Arif, Muhammad; Rahman, Shams Ur; Manan, Fazal; Khattak, Sajid Rahman; Wang, Rongyu (Frontiers in Energy Research, 2023)
It’s indispensable for the corporate sector to set aside a reasonable proportion of revenues for a sustainable corporate environment to transfer favorable and long-lasting impact to the upcoming generations. This endeavor analyzed the impact of firm performance (FP) on corporate social responsibility (CSR) of the 25 energy sector sample firms of the Shanghai stock exchange (SSE) for the period 2011-2020 in light of the role of the intervening variable, corporate governance (CG). The data of the sample firms were analyzed and tested through multiple regression and structural equation models. This study is conducted in developed economy with the rare mediator of CG that attempt to fill the gap of the previous studies conducted in a specific region of developing economies. The results show a pivotal role of FP in favorable CSR practices. Besides, the more established CG mechanism, as a mediator, has a considerable role between the predictor and predicted variables in the study. It is concluded from the results, that firms in the developed economies are more sustainability conscious than the developing countries’ firms in terms of CG and CSR practices that have been observed from the findings of the previously conducted studies in the developing nations. Furthermore, structural equation model analysis values of βs for return on assets (ROA=0.48), return on equity (ROE=0.65), return on sales (ROS=0.80), and debt-ratio (LIB=0.40) that considerably affects FP in the sample firms. It is also observed from the correlation matrix that FP indicators (ROA, ROS, ROE, and LIB) have positive as well as significant effects on CG and CSR practices. This study’s detailed policy implications are provided in the conclusion section.